Experimental Evaluation of a Novel Absorption Refrigeration system with Integrated Thermal Energy Storage and Smart Performance Monitoring - Thomas, Alexander (Cranfield University, 2025)
In Sub-Saharan Africa, unreliable electricity and inadequate cold storage infrastructure causes high post-harvest losses and vaccine storage problems. Therefore, sustainable off-grid cooling solutions are needed with solar-powered absorption refrigeration offering a promising approach, as it provides cooling driven solely by heat without reliance on grid electricity. This study evaluates a diffusion absorption refrigeration (DAR) system integrating thermal energy storage and smart monitoring. The study employs a combination of laboratory experiments and simulation modelling using TRNSYS 18 software under controlled conditions quantifying how operating inputs affect performance, focusing on COP, the impact of PCM-based storage, and acoustic diagnostics. The key finding indicate that the DAR system demonstrated a low steady-state coefficient of performance (COP) of 0.27 which is typical for small absorption systems. Despite the low COP, PCM integration significantly improved cooling signify that the system maintained cooling for extended periods of low or no solar input, preventing rapid warming. Acoustic monitoring confirmed stable operation, as consistent sound signatures indicated no cycle interruptions or anomalies. This study demonstrates the feasibility of a solar-driven DAR system with integrated thermal storage and smart monitoring for off-grid rural cooling. Despite limited efficiency, its off-grid operation and cooling retention during low-sun periods provide a valuable means to reduce uncertainty of refrigeration in remote communities. Future work should focus on improving the system’s efficiency (via design optimization or alternative working fluids) and scaling up cooling capacity. In addition. higher-performance PCMs and intelligent control strategies is also recommended to enhance system performance and reliability.
Keywords: Off-grid Cooling; Diffusion Absorption Refrigeration; Coefficient of Performance; Thermal Energy Storage; Acoustic Monitoring; TRNSYS 18 Simulation